Evaluation of a small-scale uv-treated recirculating depuration system for oysters (Crassostrea iredalei) - Sorio, Jerson C. ([Miagao, Iloilo] University of the Philippines Visayas, 2017)
Oysters are filter-feeding organisms that tend concentrate any suspended materials in its surrounding water including pathogenic bacteria. Since most oysters are eaten as raw or slightly cooked, they can act as vectors for pathogenic microorganisms and thus slightly cooked, they can act as vectors for pathogenic microorganisms and thus impose health risks to consumers (FAO, 2008). Depuration is one of the methods to reduce pathogenic bacteria in oysters to make it safe for sale and consumption. This study was was designed to evaluate the effectiveness of the small scale UV - treated recirculating depuration system manipulating different parameters such as water flow rate and tank density. It aims to determne the effect of this uv - treated recirculating depuration system in reducing pathogenic bacteria in oysters such as E. coli, Salmonella, Vibrio cholera and Vibrio parahaemolyticus, and with the survival rate and meat yield of oysters. The experiemntal results showed that the depuration system was effective in reducing E. coli at different water flow rate (15L/min, 10L/min and 5L/min), in all density level (2 oysters/L, 4 oysters/L and 6 oysters/L). However, for Vibrio parahaemolyticus and Vibrio cholera reduction, only water flow rate of 15L/min at density level of 2 oysters/L and 4 oysters/L revealed to be effective. The survival of the oysters was high in treatments with a density of 2 oysters/L. The meat yield revealed to have no sgnificant difference (P<0.01) between treatments with water flow rates. In general, treatment with water flow rate of 15 L/min in combination with 2 oysters/L density showed most promise results on all analysis. Further studies to manipulate other parameters ; e.g. salinity, temperature and testing on other pathogenic bacteria, can be conducted.
Thesis (M.S. Fisheries-Fish Processing Technology) -- [Miagao, Iloilo] : Institute of Fish Processing Technology, College of Fisheries and Ocean Sciences, University of the Philippines Visayas, June 2017.
Keywords: Oyster; Recirculating depuration system; E. coli; Vibrio cholera; Vibrio para haemolyicus